Preparation and characterization of vermicompost made from different sources of materials - Robe Elema Wako (Open Journal of Plant Science - Peertechz Publications, 2021)
The study was conducted during 2020, at Fedis district of East Hararghe Zone, Oromia National Regional State; Ethiopia. Composting is a process where waste organic materials derived from plants and/or animals are decomposed by microbial action under aeration to produce a friable homogenous product that is added to soil. Biological, chemical and physical degradation of the soil and reduced yields of the most major crops at Fadis district was the major problem of the area .This was deuto the reliance of farmers on chemical fertilizer alone, and continuous depletion of soil organic matter. Thus why this study was designed with the objectives of to prepare and characterize nutrient composition of different vermicompost and to identify quality vermicompost for crop production. Different source of materials like Wheat, Sorghum, Soybean residues, Haricot bean, Maize stock, chick pea, Finger millet, Groundnut residues, Rhodes grass and Bracharia were used to prepare vermicompost. The collected substrates were chopped and added to the worm bin. Animal manure was added to all substrates in equal amount. The ratio of 1:2was used and Pit method was used for vermi compost preparation. Composite vermi compost sample were analyzed for essential nutrients and chemical properties of compost. The Electrical conductivity of vermicompost under this study was falls in the ranges of 3.22 dS m--6.7 dS m-1 this alkalinity range is suitable for growth of most crops. According to result (Figure 1), the pH value was in the ranges of 7.2-8.4. A pH greater than 8.5 and electrical conductivity of 8 dS m-1 were found to harm both plants and earthworms. Out of all analyzed vermicompost, the highest total nitrogen (TN3.21%) was recorded from vermicompost made from ground nut, soybean (2.93%) and haricot bean (2.73%) substrates and the highest available phosphorus (787.75 mg/kgV. Compost) and 787.75mg/kg Compost) was obtained from vermicompost of haricot bean and chick pea followed by wheat (715.93) respectively. This was the tripled and doubled of TN% available in the soil and conventional compost. Their variation might be attributed to nature of different substrates. Vermi compost made from haricot bean was rich in all essential nutrients and other quality parameters and the most quality vermicompost for plant growth followed by soya bean and chick pea.